IDENTIFICATION OF SALMONELLA TYPHIMURIUM AND SALMONELLA ENTERITIDIS IN THE IMPORTED FROZEN POULTRY - Ibrahim, Mohammed M. (Science Journal of University of Zakho, 2024)
Salmonellosis, a zoonotic illness caused by Salmonella spp., is mostly transmitted to humans through the consumption of raw animal products, particularly poultry meat. Salmonella enterica serovar Typhimurium and Salmonella enterica serovar Enteritidis are the predominant strains responsible for human infection. This study aimed to assess the prevalence of S. Enteritidis and S. Typhimurium infection in frozen imported poultry using a triplex PCR technique. A total of 110 samples were chosen using the cluster sampling technique from the Ibrahim Khalil border throughout the summer and autumn of 2023. Following the cultivation of the meat samples in enrichment and selective media, suspicious colonies were obtained. Subsequently, DNA extraction was conducted, and the Salmonella isolates were identified using triplex PCR. Three (3) sets of primer pairs were utilised to target the invA gene for the Salmonella genus, the prot6 gene for the S. enteritidis serovar, and the fliC gene for the S. typhimurium serovar. The prevalence of Salmonella infection in frozen poultry meat was 12% (13 out of 110 samples). Among the contaminated samples, 38% (5 out of 13) were recognised as S. enteritidis and 30% (4 out of 13) were recognised as S. typhimurium. The findings of this finding suggest that frozen poultry meat pose a significant danger for zoonotic infections caused by S. typhimurium. and S. enteritidis.